Profiling of bean seed and variety information dissemination channels used by seed producers in Eastern and Southern Africa - Rubyogo, Jean-Claude; Aseete, Paul; Kalemer, Sylvia (2022)
Disseminating variety and technology information is important because it helps influence adoption of improved technologies thus allowing farmers exploit better genetics leading to genetic gains in farmers’ fields. Also, several farmers when they adopt new varieties may be conservative to change which makes old bean varieties dominate production systems. This is true for different crops in the developing world. For example, despite having new maize varieties, the average age of maize varieties in farmers’ fields is 15-20 years (Marcho et al., 2020), the age of rice varieties grown by farmers in India is 25 years (Marcho et al., 2020), and varietal turnover for common bean is 19 years in Ethiopia (Habte, et al., 2021). Having low variety turn over makes several dollars invested in developing new varieties go to waste since the superior varieties are not in use and not in farmer hands. Quickening variety turnover is critical for crops like common bean because it not only lift the crop’s yield potential but has also become urgent because common bean is highly vulnerable to environmental stresses that is on increase due to climate change (Atlin et al., 2017).